Manuscript (Sharh Shawahed Al-Mwashah Ala Qafiat Ibn Al-Hajeb) for Al- Shairawani - Presentation and Study - - Shaaban, Shatha Hasan; Al-Kousa, Isam Derar (Journal of Humanities & Social Sciences, 2021)
There was a lot of care and attention in the book (Al-Kafeyah) for ibn Al-Hajeb. It is a brief introduction to grammar it differs greatly from what the first grammarians classified as sibawayh, Almobared. And others and it represent a new phase of grammatical after AL Mofasal by al-Zamakhshari. scholars deal with this text explanations and endnotes. including the book tagged explaining bookmarked by (Al-Muwashah) From alkhabasi. It is one of the works that gained popularity and fame that AL-khabaisi himself could not. Because it contains grammatical issues it has become an important grammatical reference. Until his ranks approached that of a sufficient grammatical for al-Radi, and his rank exceeded the rest of the explanation. Al- Shairawani also explained the poetic evidence in the book Al-Muwashah. the research aims to Study this book – I mean explaining the evidence-and based on two sections, the first is to introduce Al- Shairawani and document the proportion of the book to him. and presentation of the approved copies of the study. and the second section , deals with studying the explanation of the evidence of the Al-Muwashah. And the reason for writing the book and its systematic organization and a statement of the author’s approach and method in arranging and dividing his book and the way he presented and explained the evidence. And the sources from which he derived his explanation. Follow the descriptive method.
Keywords: sufficient; muwashshah; explanation of evidence; method; style; sources